Managing Search Strategies for Open Innovation: The Role of Environmental Munificence as well as Internal and External R&D - Wolfgang Sofka; Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Firms compete increasingly in an open innovation environment. Search strategies for external knowledge become therefore crucial for firm success. Existing research differentiates between the breadth (diversity) and depth (intensity) with which firms pursue external knowledge source. A consensus exists that resource constrains force firms to balance both dimensions. However, relatively little is known on how managers can selectively strengthen one of these dimensions. We argue conceptually that the breadth and depth of a search strategy depends upon the nature of a firm's absorptive capacity (i.e. whether they are built through internal or external R&D activities) and the munificence of its innovation environment. We test these hypotheses empirically for a large sample of more than 8,300 firms from 12 European countries. Our empirical results show that in-house R&D strengthens the depth of a firm's search strategy while external R&D activities (e.g. contract research) increase its breadth. Moreover, we find that scarce innovation environments favor deep search strategies while breadth is more prevalent in munificent environments. We develop targeted management recommendations based on these results.
Keywords: O32; L60; 330; Open innovation; absorptive capacity; search strategies; Informationsretrieval; Strategie; Wissenstransfer; Forschung; Innovation; Forschungskooperation; Open access; EU-Staaten